Can high overall human papillomavirus vaccination coverage hide sociodemographic inequalities? An ecological analysis in Canada. Issue 16 (7th April 2016) - Drolet, Melanie; Deeks, Shelley L.; Kliewer, Erich; Musto, Grace; Lambert, Pascal; Brisson, Marc
Abstract: Background: Human papillomavirus (HPV) vaccination programs have been implemented in more than 50 countries. These programs offer tremendous promise of reducing HPV-related disease burden. However, failure to achieve high coverage among high-risk groups may mitigate program success and increase inequalities. We examined sociodemographic inequalities in HPV vaccination coverage in 4 Canadian provinces (Quebec (QC), Ontario (ON), Manitoba (MB), British Columbia (BC)). Methods: We obtained annual HPV vaccination coverage of pre-adolescent girls at provincial and regional levels, from the start of programs to 2012/2013. Regions refer to administrative areas responsible for vaccine implementation and monitoring (there are 18/36/10/16 regions in QC/ON/MB/BC). We obtained regions' sociodemographic characteristics from Statistics Canada Census. We used univariate weighted linear regression to examine the associations between regions' sociodemographic characteristics and HPV vaccination coverage. Results: Provincial HPV vaccination coverage is generally high (QC:78%; ON:80%; MB:64%, BC:69%, 2012/13). QC had the highest provincial vaccination coverage since the program start, but had the greatest inequalities. In QC, regional HPV vaccination coverage was lower in regions with higher proportions of socially deprived individuals, immigrants, and/or native English speakers ( p  < 0.0001). These inequalities remained stable over time. Regional-level analysis did not reveal inequalities in ON, MB and BC. Conclusion: School-based HPV vaccination programs have resulted in high vaccination coverage in four Canadian provinces. Nonetheless, high overall coverage did not necessarily translate into equality in coverage. Future work is needed to understand underlying causes of inequalities and how this could impact existing inequalities in HPV-related diseases and overall program success.